Metabolites of alectinib in human: their identification and pharmacological activity. Issue 7 (July 2017) - Sato-Nakai, Mika; Kawashima, Kosuke; Nakagawa, Toshito; Tachibana, Yukako; Yoshida, Miyuki; Takanashi, Kenji; Morcos, Peter N.; Binder, Martin; Moore, David J; Yu, Li
Abstract: Two metabolites (M4 and M1b) in plasma and four metabolites (M4, M6, M1a and M1b) in faeces were detected through the human ADME study following a single oral administration of [ 14 C]alectinib, a small-molecule anaplastic lymphoma kinase inhibitor, to healthy subjects. In the present study, M1a and M1b, which chemical structures had not been identified prior to the human ADME study, were identified as isomers of a carboxylate metabolite oxidatively cleaved at the morpholine ring. In faeces, M4 and M1b were the main metabolites, which shows that the biotransformation to M4 and M1b represents two main metabolic pathways for alectinib. In plasma, M4 was a major metabolite and M1b was a minor metabolite. The contribution to in vivo pharmacological activity of these circulating metabolites was assessed from their in vitro pharmacological activity and plasma protein binding. M4 had a similar cancer cell growth inhibitory activity and plasma protein binding to that of alectinib, suggesting its contribution to the antitumor activity of alectinib, whereas the pharmacological activity of M1b was insignificant.